Pengaruh Kompetensi Pedagogik Guru Terhadap Hasil Belajar Siswa Setingkat Menengah Kejuruan - Ahmad Bagus Syifaur Romli; Didit Darmawan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze how teacher pedagogical competence influences improving student learning outcomes. Efforts to improve teacher competence so that the implementation of teaching and learning activities is effective for students. This study applies literature studies, a method that utilizes sources such as journals, books, articles, and other publications to collect information. The results of the study revealed that teacher competence has a real contribution to improving student learning outcomes. The influence of teacher competence is an important factor in creating and maintaining an environment that supports student learning outcomes in order to achieve maximum learning goals.